2021
DOI: 10.1108/itp-01-2021-0008
|View full text |Cite
|
Sign up to set email alerts
|

The impact of Danmu technological features on consumer loyalty intention toward recommendation vlogs: a perspective from social presence and immersion

Abstract: PurposeThis study investigates how Danmu (danmaku) technological features (DTFs) of recommendation vlogs (rec-vlogs) impact consumer experiences and decisions.Design/methodology/approachThe authors adopt the partial least squares structural equation modeling (PLS-SEM) technique with a sample of 422 viewers of Danmu-enabled rec-vlogs to examine the proposed model.FindingsThe DTFs positively affect consumer loyalty intentions through the mediation of social presence and immersion. Also, vlogger-product congruenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 91 publications
(169 reference statements)
1
12
0
Order By: Relevance
“…Previously, Korzaan and Boswell (2008) explored the positive impact of social presence on immersion experience. Yang et al (2021) confirmed the effect of social presence on immersion in the context of vlogs. When consumers are immersed in a virtual shopping environment, they will experience a pleasant and immersive state (Sun et al, 2019).…”
Section: The Mediating Role Of Immersive Experiencesupporting
confidence: 59%
“…Previously, Korzaan and Boswell (2008) explored the positive impact of social presence on immersion experience. Yang et al (2021) confirmed the effect of social presence on immersion in the context of vlogs. When consumers are immersed in a virtual shopping environment, they will experience a pleasant and immersive state (Sun et al, 2019).…”
Section: The Mediating Role Of Immersive Experiencesupporting
confidence: 59%
“…Previous research has focused mainly on the mediating role of immersion in various activities. For instance, Yang et al (2021) examined the mediating effect of immersion between social presence and customer loyalty intentions toward recommendation vlogs. Their findings confirm the proposed hypothesis and indicate that increased consumer immersion positively influences customer loyalty.…”
Section: Theoretical Framework and Hypothesis Developmentmentioning
confidence: 99%
“…Similarly, through a scenario-based experiment conducted with 462 participants, researchers demonstrated that the live streaming strategy with social presence cues induces a more authentic consumer viewing experience than a prerecorded strategy, which further increases consumers' searching and subscribing intention (Ang et al , 2018). As suggested by previous research, video with bullet screens can enhance consumers' perception of social presence (Yang et al , 2021). In our context, we further measure and test the social impact of the barrage system on user interaction.…”
Section: Theoretical Backgroundmentioning
confidence: 83%
“…While watching a video, viewers receive the cumulative barrage posted by other viewers. The bullet screens displayed synchronously with video content on screen provide a co-viewing experience that may make the viewers perceive the presence of others (Yang et al, 2021) and thus acquire a sense of belonging (Xiang and Chae, 2021). In accordance with social impact theory (Latane and Wolf, 1981), scholars proposed that people were impacted by the social presence of other people, and with the increase in the number of people, the effects of social presence gradually increase and lead to individual behavior convergence.…”
Section: Influence Of Barrage Fluctuation Amplitude On User Interactionmentioning
confidence: 99%
See 1 more Smart Citation